Choosing Ayurveda as a healthcare practice in Argentina - Freidin, Betina (2015)
This article analyzes the process of adoption of Ayurveda as a healthcare practice in Buenos Aires, focusing on sociocultural dimensions and material aspects which either facilitate or discourage the following of this foreign medical tradition. Ayurveda is an ancient Indian medicine whose popularity has been on the rise among the Argentinean middle and upper classes. Introduced as a ‘lifestyle’ medicine, it resonates with the new health consciousness of individual responsibility in health maintenance and improvement. Based on in-depth interviews conducted with 20 followers of Ayurveda in Buenos Aires, the article shows that it attracts New Agers, adherents to food-driven subcultures, and patients dissatisfied with the limitations of biomedicine. Followers develop new skills for self-understanding, self-healing, and wellbeing. As adherents to a foreign medical approach, however, they adopt Ayurvedic practices in flexible ways, and some even hold critical views on the elitist market niches of Ayurvedic specialists and products.